Factors Related to Community Compliance with COVID-19 Health Protocols in Pardomuan I Village, Samosir Regency - Sinaga, Lusi Veronika; Nababan, Donal; Netti Etalia br Brahmana (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to determine the factors associated with community compliance with COVID-19 health protocols in Pardomuan I Village, Samosir Regency. This study is an analytical survey with a cross-sectional approach. This study was conducted in Pardomuan Village with a population of all heads of households and a sample size of 171 households from May to September 2021. Data were collected through interviews using a questionnaire and analyzed using the Chi-Square statistical test and binary logistic regression analysis. The results showed that there was a relationship between knowledge, attitude, level of awareness, age, and education with community compliance with COVID-19 health protocols in Pardomuan I Village, Samosir Regency, and that there was a relationship between gender and community compliance with COVID-19 health protocols in Pardomuan I Village, Samosir Regency. From the binary logistic regression test, it can be seen that the variables with the greatest influence are level of awareness, attitude, knowledge, education, age, and gender. It is hoped that the village authorities will collaborate with the community health center to conduct outreach on the COVID-19 Health Protocol to increase knowledge, change attitudes, and raise awareness among the community in implementing the COVID-19 Health Protocol. It is hoped that the community of Pardomuan I Village will comply with the COVID-19 Health Protocol so that the transmission of COVID-19 can be prevented and accurate information related to COVID-19 and the implementation of the COVID-19 Health Protocol can be obtained. -19